Genetic diversity of native potatoes (Solanum spp.) from Vilcashuaman district, Ayacucho- Peru, using AFLP - Remón Gamboa, Yessenia K. (2018)
In this article, using the Amplified Fragment Lenght Polymorphism (AFLP) technique, we evaluated the genetic diversity of 30 native potatoes morphotypes from Vilcashuaman, Ayacucho. DNA extraction was done with the modified CTAB method, using fresh leaves of greenhouse plants of two weeks age. From 200 mg of plant tissue, it was posible to obtain between 300 and 500 ng/μLof good quality DNA. The enzymatic digestion of the DNA was carried out using EcoRI and MseI, and 12 combinations of primers were used, from which the two most polymorphic combinations were chosen (E13 – M49 and E38 - M49). The statistical analysis was done with the NTSYs 2.10 program using the Simple Matching coefficient, obtaining values of PIC (polymorphic content index) of 0.45 and 0.40 for the combinations E38 – M49 and E13 – M49, respectively. In total, 68 clearly differentiable bands were identified, of which 55.8% were polymorphic bands. The cluster analysis according to the UPGMA algorithm originated a dendrogram with a cofenetic correlation index of r = 0.7; at a coefficient of similarity of 0.6, eight genetic groups were established and at a coefficient of 1, no duplicate morphotypes were found. The results obtained show the high informative power of the AFLP and the high variability of the native potatoes studied.